Technology Readiness, Social Influence, and Anxiety as Predictors of University Educators’ Perceptions of Generative AI Usefulness and Effectiveness (Journal of Education and Development, 2025)
Background: Generative Artificial Intelligence (genAI) tools, such as ChatGPT, hold promise for higher education but also raise valid concerns. Critical questions arise regarding university educators’ attitudes toward the growing use of genAI in education. This multinational study aimed to examine the determinants of genAI Perceived Usefulness and Effectiveness among educators in Arab universities Methods: The study applied the validated Technology Acceptance Model (TAM)-based theoretical framework using the Ed-TAME-ChatGPT survey instrument. Data were collected using a self-administered structured online questionnaire distributed in November–December 2024 via SurveyMonkey platform. Results: The final sample comprised 685 academics across the Gulf Cooperation Council countries, Levant/Iraq, Egypt/Sudan, and the Maghreb countries. In multivariate analyses, Social Influence (β = 0.445 and 0.531, p <